2022
DOI: 10.1007/s10834-022-09848-x
|View full text |Cite
|
Sign up to set email alerts
|

The Social and Economic Impact of Covid-19 on Family Functioning and Well-Being: Where do we go from here?

Abstract: A growing body of research demonstrates that COVID-19 has had a profound impact on family functioning and well-being in a range of countries. The fear and uncertainty of the health risks, in addition to the stress from ensuing restrictions and constraints on everyday life caused major disruptions, impacting the financial, emotional, and physical well-being of adults and children alike. In this report, we summarize the current literature on the impact of COVID-19 disruption to family functioning and economic we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 65 publications
2
31
0
1
Order By: Relevance
“…The cross-sectional design, with a subjective perception by the patients about worsening or improvement on migraine days, cannot be compared with previous and present data since neither used a migraine diary to assess the reliability of provided answers. Hence, a few publications using a migraine diary were performed in Latin American countries, including Chile and Argentina [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cross-sectional design, with a subjective perception by the patients about worsening or improvement on migraine days, cannot be compared with previous and present data since neither used a migraine diary to assess the reliability of provided answers. Hence, a few publications using a migraine diary were performed in Latin American countries, including Chile and Argentina [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, findings from this study and others provide implications for practitioners seeking to promote family flourishing during times of stability as well as upheaval. First, it is important to recognize that experiencing major stressors is likely to increase negative processes in relationships, including hostility, withdrawal, and less responsive support (Andrade et al, 2022). In the present study, stressor pileup was associated with lower couple relationship satisfaction and, in turn, higher stress for parents.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, financial difficulties can have an impact on the family dynamics and relationships, which are crucial for adolescents' well-being (van Harmelen et al ., 2016). Ample studies have shown that the current pandemic has brought financial constraints on families resulting in negative connotations on students’ health (Andrade, Gillen, Molina, & Wilmarth, 2022; Kim et al ., 2022; Rodrigues, Silva, & Franco, 2021). Students’ perceive a lack of family support due to frustration and unfriendly home environment which makes them reluctant to vent out their feelings leading to poor mental health tendencies (Yu et al ., 2015).…”
Section: Discussionmentioning
confidence: 99%